Odpowiedź:
[tex] \sqrt[3]{3 \frac{3}{8} } + x - {(1 - 2 \frac{1}{4} )}^{2} = 13 \frac{7}{16} \\ \sqrt[3]{ \frac{27}{8} } + x - {( - 1 \frac{1}{4} )}^{2} = 13 \frac{7}{16} \\ \frac{3}{2} + x - {( - \frac{5}{4} )}^{2} = 13 \frac{7}{16} \\ 1 \frac{1}{2} + x - \frac{25}{16} = 13 \frac{7}{16} \\ 1 \frac{1}{2} + x - 1 \frac{9}{16} = 13 \frac{7}{16} \\ x = 13 \frac{7}{16} - 1 \frac{1}{2} + 1 \frac{9}{16} \\ x = 13 \frac{7}{16} - 1 \frac{8}{16} + 1 \frac{9}{16} \\ x = 13 \frac{8}{16} = 13 \frac{1}{2} [/tex]